Tejidos hospitalarios : ÅPuede una estación de metro contribuir a la conformación de un centro metropolitano de salud? (2016)
"The Project is located in a district called Kennedy, more specific, in a sector called Kennedy central. There are three main arguments which I based my choice on. The first one is that is has a level III hospital of complexity of a great scale that had lack of equipment to complement it. The second one is that the little amount of equipment that area has are formed in and informal and disarticulated way. The third and last is that between them it is located the Kennedy metro station, which helps to integrated them. The project will have an elevated bridge that lineally connect the hospital, with the metro station and in the other side to the building. The question that helped throw the investigation and realization of the Project is ¨how should a metropolitan center of medical serviced be conformed, that also count with an elevated metro station?"-- Tomado del Formato de Documento de Grado.